Presentation basics - Fullmer, Donna Lynne, ....- (New York : Fairchils Books, 2014)
Presentation Basics helps students hone both of the critical aspects of successful presentation—visual and verbal skills. Writing from the viewpoint that an effective presentation requires much more than adept graphic representation, Fullmer helps students strengthen their verbal skills to sell their ideas. The book also takes an essential look at business etiquette and body language, stressing the impact of these factors on a presentation.